Relevansi Ayat-Ayat Al-Quran Tentang Musyawarah - Rizka Fauziah; Rachmad Risqy Kurniawan (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
The purpose of this study is to explain the relevance of the verses of the Qur'an regarding musyawarah. This research is a library research using literature (library) as a source, among others, books of interpretation and other supporting scientific articles. The interpretation method used in this research is the maudu'i (thematic) research method and the tahlili (analytic) interpretation method. Based on this research, it can be concluded that the relevance of the verses of the Qur'an regarding musyawarah is to explain the purpose and reasons for the choice to consult, namely for and because it can unite everyone, solve important problems or problems, produce the best solutions and decisions. from various options, to avoid harm and realize mashlahah for everyone, including those who do not participate in the musyawarah, and is the best way, maybe even the only way for believers to make decisions about their affairs.